Peran Manajemen Pengambilan Keputusan di Sekolah - Lucky Tirta Nurarfiansyah; Agung Muhammad Nur; Maidiana Maidiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Decision making is an activity carried out by a person or group to choose an option from several available options based on consideration and evaluation of existing information. The purpose of this research is to find out how the role of decision-making management in schools. The results found that decision-making management is very important because decision-making will determine the direction, quality and effectiveness of education in the school.